Vascular epilepsy in adulthood: current status and outlook for research and management Vaskuläre Epilepsie im Erwachsenenalter: aktueller Stand und Ausblick für Forschung und Management - Stefan, Hermann; Hammen, Ernst Thilo; Punia, Vineet (Clinical Epileptology, 2025)
Background: Vascular epilepsies can manifest at various stages of adulthood and are often accompanied by age-related comorbidities. Aging processes, particularly vascular and neurodegenerative changes, contribute significantly to the risk of late-onset epilepsy (LOE). Methods: This narrative review explores the emerging role of the glymphatic system in the pathogenesis of vascular-related adult-onset epilepsy in the context of aging. Both established antiseizure medications (ASMs) and novel preventive strategies currently under investigation are evaluated. Results and conclusion: The review emphasizes the importance of an interdisciplinary management approach and discusses practical considerations for optimizing care in this patient population.
CRIS-Team Scopus Importer:2025-10-03
Keywords: Aging; Biomarker; Diagnosis; Glymphatic system; Treatment